Chronic lymphocytic leukaemia induces an exhausted T cell phenotype in the TCL1 transgenic mouse model. (4th May 2015) - Gassner, Franz J.; Zaborsky, Nadja; Catakovic, Kemal; Rebhandl, Stefan; Huemer, Michael; Egle, Alexander; Hartmann, Tanja N.; Greil, Richard; Geisberger, Roland
Summary Although chronic lymphocytic leukaemia (CLL) is a B cell malignancy, earlier studies have indicated a role of T cells in tumour growth and disease progression. In particular, the functional silencing of antigen‐experienced T cells, called T cell exhaustion, has become implicated in immune evasion in CLL. In this study, we tested whether T cell exhaustion is recapitulated in the TCL1tg mouse model for CLL. We show that T cells express high levels of the inhibitory exhaustion markers programmed cell death 1 (PDCD1, also termed PD‐1) and lymphocyte‐activation gene 3 (LAG3), whereas CLL cells express high levels of CD274 (also termed PD‐ligand 1). In addition, the fraction of exhausted T cells increases with CLL progression. Finally, we demonstrate that exhausted T cells are reinvigorated towards CLL cytotoxicity by inhibition of PDCD1/CD274 interaction in vivo. These results suggest that T cell exhaustion contributes to CLL pathogenesis and that interference with PDCD1/CD274 signalling holds high potential for therapeutic approaches.